Acompanhamento do processo produtivo do carbonato de cálcio na mineração Ouro Branco – Governador Dix-Sept Rosado/RN - Soares, Ana Lorena de Brito (Universidade Federal Rural do Semi-Árido, 2019)
Calcium carbonate is a very abundant compound in Brazil. The region of Chapada do Apodi counts on a great extension of limestone in all its territory, being the RN the holder of the largest reserve in Brazil. This product is found in the market in different grades, and is used for the most different purposes, from the manufacture of ceramics or glasses, even the use in animal feed. Even with this wide range of applications, the production process of Ground Calcium Carbonate (GCC), is not evolving, being very little studied, so, the present work aims to describe its manufacturing process with Mineração Ouro Branco, which is located in the municipality of Governador Dix-Sept Rosado - RN. Also described are the main laboratory tests performed by the company's quality control, which are of fundamental importance for a final product of high quality and good competitiveness in the market
Relatório
Keywords: Carbonato de cálcio; Processo; Análises; Calcium carbonate; Process; Calcium carbonate; tests; ENGENHARIAS::ENGENHARIA QUIMICA